Perceptions of time at work: why the clock ticks differently for men and women when they are not working at work - Ferreira, A.; Esteves, J. D. (Personnel Review, 2016)
Purpose - Activities such as making personal phone calls, surfing on the internet, booking personal appointments or chatting with colleagues may or may not deviate attentions from work. With this in mind, the purpose of this paper is to examine gender differences and motivations behind personal activities employees do at work, as well as individuals' perception of the time they spend doing these activities. Design/methodology/approach - Data were obtained from 35 individuals (M-age=37.06 years; SD=7.80) from a Portuguese information technology company through an ethnographic method including a five-day non-participant direct observation (n = 175 observations) and a questionnaire with open-ended questions. Findings - Results revealed that during a five-working-day period of eight hours per day, individuals spent around 58 minutes doing personal activities. During this time, individuals engaged mainly in socializing through conversation, internet use, smoking and taking coffee breaks. Results revealed that employees did not perceive the time they spent on non-work realted activities accurately, as the values of these perceptions were lower than the actual time. Moreover, through HLM, the findings showed that the time spent on conversation and internet use was moderated by the relationship between gender and the leisure vs home-related motivations associated with each personal activity developed at work. Originality/value - This study contributes to the literature on human resource management because it reveals how employees often perceive the time they spend on non-work related activities performed at work inaccurately. This study highlights the importance of including individual motivations when studying gender differences and personal activities performed at work. The current research discusses implications for practitioners and outlines suggestions for future studies.